Transformation of the airy pulse at temporary jump of the dielectric permittivity of the medium - Nerukh, A.G.; Kuryzheva, O.V. (Radiotekhnika, 2018)
The spatio-temporal problem of interaction of the Airy electromagnetic pulse and a plane dielectric layer is solved in the case of a permittivity sharp change in a layer at zero moment of time. Expressions for the field inside the layer are obtained and the influence of the starting parameter on the position of the pulse inside the layer is shown. The evolution of the pulse in media with different refractive index is analyzed. A comparative analysis of the interaction of the Airy pulse with a plane layer between two dielectric media with a dielectric layer is carried out. The influence of pulse reflections from the layer boundaries on its shape and location is analyzed. From the analysis of the obtained results it follows that the choice of the initial space-time parameter affects the location of the pulse in the layer, and the transition of the signal to a medium with a larger (lower) permittivity results in the amplitude increase of oscillations and the main lobe shape change.